Space shuttle Challenger: how safety and risk were overlooked - Austin, Laurel C. (Henry Stewart Talks, 2017)
This case study defines what is meant by ‘risk’ in a business setting and explains how the lack of a robust risk management system enabled the Challenger space shuttle to be launched despite serious safety concerns on the part of some engineers.